2021
DOI: 10.1371/journal.pone.0260946
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of land use practices to GHGs in the Canadian Prairies crop sector

Abstract: The global crop sector is estimated to contribute about 10.4% of global GHGs annually. The Canadian crop sector is assessed as adding about 6.5% to total national emissions. These estimates over report the impact of farming as they ignore the complex interaction of cropping with the environment and the role land use, land use change and forestry (LULUCF) play in sequestering carbon. This study quantifies the contribution of land use to GHG emissions and removals in the Canadian Prairies crop sector between 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study by Grant et al 39 investigated how changes in management practices affect GHG emissions, finding that the average net reduction in emissions from converting to zero tillage was 0.61 Mg CO 2 equivalents per ha, per year in Canada. As noted above, Awada et al 18 found the sustainable practices that combine better tillage and new genetics led to an 80% decline in GHG emissions in the Canadian prairie crop sector between 1985 and 2016. After 2005, emissions dropped 53%, more than is required to meet the 2030 Paris Accord target.…”
Section: Insights From the Literature On The Role Of Agricultural Bio...mentioning
confidence: 92%
See 1 more Smart Citation
“…A study by Grant et al 39 investigated how changes in management practices affect GHG emissions, finding that the average net reduction in emissions from converting to zero tillage was 0.61 Mg CO 2 equivalents per ha, per year in Canada. As noted above, Awada et al 18 found the sustainable practices that combine better tillage and new genetics led to an 80% decline in GHG emissions in the Canadian prairie crop sector between 1985 and 2016. After 2005, emissions dropped 53%, more than is required to meet the 2030 Paris Accord target.…”
Section: Insights From the Literature On The Role Of Agricultural Bio...mentioning
confidence: 92%
“…There is an abundance of literature on changes in land use, reductions in GHG emissions and increases in carbon sequestration, but little of this literature frames the changes specifically as resulting from the adoption of GM crops. Awada et al 18 for example, built a model to account for different farming practices (i.e., conventional, minimum and zero tillage, summerfallow, crop rotations and residue retention) and input usage rates (i.e., fertilizer and fuel) to estimate how they affect GHG emissions in different soil climate zones and provinces in the Canadian prairies region. The adoption of sustainable practices led to an 80% decline in GHG emissions in the crop sector between 1985 and 2016.…”
Section: Insights From the Literature On The Role Of Agricultural Bio...mentioning
confidence: 99%
“…The Western region in Canada is dominated by the Prairie ecozone which occurs mostly between latitudes of 49° and 54°N, comprises more than 80% of the national agricultural land or 52 Mha (of which ∼60% is cropland), receives most of the N fertilizer used (∼75%) and grows nearly all the canola, spring wheat, and barley produced in Canada (Awada et al., 2021; Statistics Canada, 2016, 2022). The region is characterized by its aridity with an annual average precipitation ranging from 300 to 550 mm (McGinn, 2010) and long winters with approximately 150 soil freezing days and 5–15 freeze‐thaw cycles (Henry, 2008) There are five soil zones in this region (Brown, Dark‐brown, Black, Gray and Dark‐gray) with a general precipitation gradient along these soil types and contrasting soil organic matter values (higher for the Black zone at 5%–10% and lower for the Brown zone soils at 2%–5%) (Awada et al., 2021). The diversity in climatic and soil conditions implies that the drivers of freeze‐thaw cycle emissions and the importance of freeze‐thaw events to annual totals could vary considerably across the Prairies.…”
Section: Introductionmentioning
confidence: 99%